HOMBO BATU AS A SOURCE OF KNOWLEDGE-BASED ECONOMIC DEVELOPMENT - Darmawan Harefa (Curve Elasticity: Jurnal Pendidikan Ekonomi, 2026)
Hombo Batu, also known as Fahombo, is a stone-jumping tradition of the Nias people that holds significant cultural value and has been passed down through generations. This tradition not only reflects the community’s bravery, solidarity, and social identity but also holds substantial potential to be developed as a knowledge-based economic resource. This study employs a literature review approach to analyze scientific literature related to Hombo Batu in the contexts of culture, education, and creative economy, focusing on publications from 2020 to 2025. The review examines the relationship between the tradition, contextual science (ethnoscience), and economic opportunities through cultural tourism, experiential learning, and the development of knowledge-based products. The results indicate that Hombo Batu can serve as a medium for science education, including physics concepts such as force, kinetic energy, and projectile motion, thus providing strong educational value. Moreover, this tradition has the potential to support local economic development through cultural tourism, culturally-based training, and creative products that combine education with cultural experience. The synergy between culture, science, and creative economy allows Hombo Batu to become a sustainable economic resource while preserving the cultural identity of the Nias community. This study emphasizes the importance of integrating local wisdom with scientific knowledge in efforts to develop a knowledge-based economy.